2015
DOI: 10.1071/en14210
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic composition of polyhalomethanes from marine macrophytes – systematic effects of the halogen substituents on isotopic composition

Abstract: Environmental context. Once released to the atmosphere, halocarbons are involved in key chemical reactions. Stable carbon isotope measurements of halocarbons can provide valuable information on their sources and fate in the atmosphere. Here, we report d 13 C values of 13 polyhalomethanes released from brown algae, which may provide a basis for inferring their sources and fate in future studies.Abstract. Halocarbons are important vectors of reactive halogens to the atmosphere, where the latter participate in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Other sources of nHCs are microalgae and bacteria in sea ice ,, and frost flowers on sea ice . Production also occurs by reaction of dissolved organic matter (DOM) with oxidized halogen species at the air–ice interface and enzyme-mediated reactions with DOM in seawater. ,, Carbon isotopic composition has been suggested as a tool for discriminating nHCs produced by macroalgae, phytoplankton, and reactions of DOM …”
Section: Producers and Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other sources of nHCs are microalgae and bacteria in sea ice ,, and frost flowers on sea ice . Production also occurs by reaction of dissolved organic matter (DOM) with oxidized halogen species at the air–ice interface and enzyme-mediated reactions with DOM in seawater. ,, Carbon isotopic composition has been suggested as a tool for discriminating nHCs produced by macroalgae, phytoplankton, and reactions of DOM …”
Section: Producers and Sourcesmentioning
confidence: 99%
“…27,35,36 Carbon isotopic composition has been suggested as a tool for discriminating nHCs produced by macroalgae, phytoplankton, and reactions of DOM. 37 The nHCs produced by marine phytoplankton were reviewed and species grouped by tropical, subtropical, temperate, and polar zones. 17 The number of nHC compounds reported in a particular study varied from 1 to 11, which might be characteristic of the producing species or simply to the suite selected for analysis.…”
Section: Producers and Sourcesmentioning
confidence: 99%
“…Bahlmann et al [12] reported d 13 Cvalues of polyhalomethanes released from three brown algae species (Laminaria digitata, Fucus vesiculosus, F. serratus) and one seagrass species (Zostera noltii). d 13 C values for CHCl 3 and CHI 2 Br from laboratory incubations under variable light and water level conditions showed a systematic effect of the halogen substituents that could empirically be described in terms of linear free energy relationships (LFER) and may be used in future to discriminate between different marine sources.…”
mentioning
confidence: 99%